STUDY OF FACTORS AFFECTING THE HEALTH STATUS OF BREASTFEEDING WOMEN AND THEIR INFANTS - Rai, रोहिणी; Badaik, शान्ता (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nutrient deficiency in breastfeeding women is a serious problem, which not only affects the health of mothers but also has far-reaching effects on the development and health of their infants (0-12 months). This study analyses the nutritional status of breastfeeding women in Dhanbad district, their health and its impact on the health of infants. The research highlights the causes, effects and possible solutions of nutrient deficiency.